Does digital financial inclusion matter for firms’ ESG disclosure? Evidence from China - Lu, Yichun; Wang, Liang; Zhang, Yu (Frontiers in Environmental Science, 2022)
Using a sample of Chinese listed firms during 2010–2018, this paper examines the relationship between digital financial inclusion and firms’ ESG disclosure. The results show that (1) digital financial inclusion can significantly promote firms’ ESG disclosure; (2) the promotion effect of digital financial inclusion on firms’ ESG disclosure occurs mainly through channels including the coverage breadth and usage depth; (3) for firms with higher financing constraints and state-owned enterprises, the promotion effect of digital financial inclusion on firms’ ESG disclosure is more prominent. This paper provides relevant conclusions and insights for promoting firms’ ESG information disclosure, integrating the digital economy, and encouraging innovation development.